Employee Engagement of Influencer Generation: The Role of Employee Voice, Organizational Culture, and Career Development - Benaya, Joseph Onesiforus; Nursanti, Tinjung Desy (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
It is the goal of this research to figure out the extent to which elements such as employee voice, organizational culture, and career development have an impact on employee engagement among Influencer Generation, or generation Z as it is more commonly referred to.  In this study, a quantitative methodology is utilized, and the participants are members of Influencer generation who are now employed. For the purpose of this investigation, the application SmartPLS version 4 and the Structural Equation Model (SEM) are utilized for the processing and analysis of the data. According to the findings of the analysis of the data, the factors of career development, corporate culture, and employee voice all have positive and significant effects on employee engagement. Due to the fact that these aspects have an effect on employee engagement, which in turn can lead to increased economic performance, researchers propose that organizations pay attention to employee voice, organizational culture, and career development.